An advanced model of consumer attitudes toward advertising on the mobile internet. (4th December 2006) - Haghirian, Parissa; Inoue, Akihiro
Advertising on the mobile internet is considered as an influential new marketing channel in the new future. So far technological limitations inhibit its optimised usage in Europe and the US, whereas in Japan constant access to the internet via mobile devices is already a reality. This paper therefore discusses the relevance of advertising on the mobile internet as a marketing tool and investigates antecedents of Japanese consumer attitudes toward this new advertising channel. The analysis is based on a Japanese consumer survey. The results indicate that informativeness and credibility of the advertising message have the greatest impact on consumers' attitude towards advertising on the mobile internet.